1982
DOI: 10.1088/0031-9155/27/4/003
|View full text |Cite
|
Sign up to set email alerts
|

The in situ measurement of strontium content in bone using X-ray fluorescence analysis

Abstract: A technique is described which uses x-ray fluorescence to determine in situ the strontium content of bone. Measurements were made of the skulls of seven rabbits both before and after a single bolus injection of strontium was administered intravenously. The retention of strontium was followed for up to eight months and could be represented either by a three-exponential model or, for data obtained between 12 and 252 d following injection, the power function At-b, where t is the time in days following injection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…In vivo, the overlying tissue thickness can be determined ultrasonically with an accuracy of 0.3 mm with the use of a 7 MHz ultrasound transducer (12). Alternatively ; the measured signal can be normalized with respect to coherently and incoherently scattered radiation (13). An improved response to the Sr signal can be attained by using polarized radiation to excite the Sr characteristic radiation (12) .…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, the overlying tissue thickness can be determined ultrasonically with an accuracy of 0.3 mm with the use of a 7 MHz ultrasound transducer (12). Alternatively ; the measured signal can be normalized with respect to coherently and incoherently scattered radiation (13). An improved response to the Sr signal can be attained by using polarized radiation to excite the Sr characteristic radiation (12) .…”
Section: Discussionmentioning
confidence: 99%
“…As for Sr, four bone Sr IVXRF systems have been reported to date. Snyder and Secord (1982) modeled Sr retention in the skull of seven rabbits after the administration of Sr intravenously. Using Cd-109 as the excitation source and a 80mm 2 X 5mm 2 Kevex Si(Li) detector as the detection system, they obtained the biological half-lives for radioactive strontium.…”
Section: Bone Sr In Vivo X-ray Fluorescencementioning
confidence: 99%
“…Snyder and Secord measured bone strontium in rabbits [43] and, in a totally separate development, Wielopolski and his colleagues demonstrated that they were able to measure bone strontium in human subjects [44]. However, neither of these initiatives were followed up in the respective laboratories.…”
Section: In Vivo X-ray Fluorescence Of Bone Strontiummentioning
confidence: 99%